2019
DOI: 10.1371/journal.pone.0215373
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Childbirth Experience Questionnaire (CEQ) in China: A multisite cross-sectional study

Abstract: Background The childbirth experience of women represents a significant aspect of quality care. Due to the lack of a reliable Chinese language tool for assessing childbirth experiences, examples must be adapted from other countries. The aim of this study was to translate an English version of the Childbirth Experience Questionnaire (CEQ) into Chinese and adapt this tool to the Chinese context. Methods A questionnaire validation study was conducted. A forward-backward tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
54
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 33 publications
14
54
2
2
Order By: Relevance
“…those with instrumental births, those in labour in excess of 12 h, and those who had their labours augmented with oxytocin). The CEQ has since been translated and validated in several languages [19][20][21][22][23], and has been successfully implemented in empirical studies including a large variety of culturally diverse samples [24][25][26][27][28][29][30]. However, measurement instruments always hold potential for improvement, and in validating the original Swedish version of the instrument, two domains showed weaker performance; Participation and Professional Support [18].…”
Section: Introductionmentioning
confidence: 99%
“…those with instrumental births, those in labour in excess of 12 h, and those who had their labours augmented with oxytocin). The CEQ has since been translated and validated in several languages [19][20][21][22][23], and has been successfully implemented in empirical studies including a large variety of culturally diverse samples [24][25][26][27][28][29][30]. However, measurement instruments always hold potential for improvement, and in validating the original Swedish version of the instrument, two domains showed weaker performance; Participation and Professional Support [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding prolonged labor and birth experience show conflicting results. Some researchers have found that women with long labors had an increased risk of a negative birth experience [8][9][10][11][12][13], while others did not find such an association [14,15]. A negative birth experience might lead to women avoiding childbearing [12] or wanting an elective cesarean section in a subsequent pregnancy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Active labor is usually defined as the period from 4 cm dilatation of the cervix until the baby is born [8,10,11,14]. However, there are other aspects of labor progression that may be of importance for the birth experience, such as the duration of early labor (cervix dilated 1-4 cm, often defined as the latent phase).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results were in line with previous studies validating other translations of the CEQ. Other studies have increased the response rate using reminders (4, 7), use of a web questionnaire or administering the questionnaire during hospitalization immediately after delivery (8,9). However, sending reminders may result in delayed response, which in turn may affect the item responses (15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, three items in Chinese CEQ were moved to another domain. High ceiling effect was observed especially in items regarding labor pain, which the authors attributed to Chinese traditions of accepting intense labor pain as normal and lower analgesia use compared to Western countries (8). The Persian translation was not subject to structural changes, but the item evaluating midwife's support for partner was seen as irrelevant, as partners are not allowed in deliveries in Iran (9).…”
Section: Discussionmentioning
confidence: 99%